Daphnia Pulex의 현장적용을 위한 최적의 배양조건 연구 - 이종준; 김태훈; 권동민; 박재로; 최이송; 오종민 (한국수처리학회지, 24(1), 2016)
Recently, algae concentration in the river and lake has been increasing continuously and in a rapid speed. Algae can be a discomfort to people and the secretion of toxic substances can adversely affect the ecosystem. There is a need to develop and apply improved water quality technologies in the environment to help to reduce the confusion that provoke the algae in the ecosystem. We studied the optimal conditions of Daphnia to apply it in the field of water improvement, by determining the optimum conditions that can be cultured in Daphnia, via the control of oxygen supply temperature and food to apply in fields of culture techniques. In this study it was found that the best set feeding food is 22 ml, with a final population of 1960 inds/L. In the aeration of the experiment, it was found that the most efficient DO concentration was 5.2 mg/L with an individual number of Daphnia of 1,200 inds/L. Regarding the water temperature, it was found that a range from 24℃ to 26℃ was the most appropriate the temperature of room cultured that doesn’t effect the scattering to increase the activity was determined to be 25℃. KCI Citation Count: 0